Optically based quantification of fluxes of mercury, methyl mercury, and polychlorinated biphenyls (PCBs) at Berry's Creek tidal estuary, New Jersey. (19th September 2018) - Chang, G.; Martin, T.; Whitehead, K.; Jones, C.; Spada, F.
Abstract: Berry's Creek is an urban tidal estuary of the Hackensack River (New Jersey, U.S.A.), with over 10 km of waterways and over 3 km 2 of tidal marsh. More than a century of industrial activity has resulted in elevated contaminant concentrations in sediment, water, and biota. Mercury, methyl mercury, and polychlorinated biphenyls (PCBs) have been identified as the primary chemicals of concern (COCs) due to their persistence and bioaccumulation potential in aquatic and nearshore wildlife. As part of a multi‐phased remedial investigation program, OPTically‐based In‐situ Characterization System (OPTICS) field studies were conducted in Berry's Creek to characterize water column contaminant dynamics, specifically to (1) improve understanding of the interrelationship(s) between surface sediment and water column contaminants and (2) quantify the transport of water column COCs between waterways and marshes. Results from OPTICS monitoring indicated that particulate resuspension from the upper 5 mm of the sediment bed during flood and ebb tides and storm flows is the primary process by which COCs are exchanged from bedded sediment to the water column. Analysis of mass exchange of COCs indicated that COCs associated with resuspended particulates are transported from the waterways to the marshes, where they are retained. Dissolved COC exchange from marshes to the waterways was minor (less than 8% of total COC mass in water). Overall, marshes were observed to be net sinks for COCs.